A Novel Magnetic Field Device for Inducing Hyperthermia Using Magnetic Nanoparticles - Dürr, Stephan; Schmidt, Oliver; Janko, Christina; Kraemer, H P; Tripal, Philipp; Eiermann, F; Tietze, R; Lyer, Stefan; Alexiou, Christoph (Biomedizinische Technik, 2013)
A new alternating current (AC) magnetic field applicator was designed to induce hyperthermia in an animal tumour model using superparamagnetic iron oxidenanoparticles (SPION). First experiments on phantoms including different concentrations of SPION were conducted.The results confirmed that the new AC magnetic field applicator could heat-p SPION. This proofs the capability to induce hyperthermia by SPION, dependent on the concentration
EVALuna2:19922
Keywords: Magnetic drug targeting; nanoparticles; alternating current magnetic field; hyperthermia